2014
DOI: 10.1108/bfj-06-2014-0207
|View full text |Cite
|
Sign up to set email alerts
|

Rising use of “food aid” in the United Kingdom

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm: 412925 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 10 publications
6
82
0
Order By: Relevance
“…Similar patterns of cuts and austerity measures are also present in many American States. In the UK, there is an increasing need for food aid (Lambie‐Mumford & Dowler, ), and there are significant problems of fuel poverty (Roberts, Vera‐Toscano, & Phimister, ). In addition to any potential physical impacts of this, there are often psychological and emotional implications.…”
Section: Introductionmentioning
confidence: 99%
“…Similar patterns of cuts and austerity measures are also present in many American States. In the UK, there is an increasing need for food aid (Lambie‐Mumford & Dowler, ), and there are significant problems of fuel poverty (Roberts, Vera‐Toscano, & Phimister, ). In addition to any potential physical impacts of this, there are often psychological and emotional implications.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, avoiding waste is underpinned by a variety of social norms, behaviours and conventions, including, amongst others: sharing, caring, gifting, re-use and recycling. There is a growing body of literature exploring food sharing practices, from 'pot-luck' arrangements and commensality [64]; to community food gardens [65], organised food swapping events as part of local sharing economies [66], and those noting the rise of the food banks in the UK [67,68]. However, other than Julier's [64] work, such studies focus on organised, collective arrangements, rather than small scale, domestic practice.…”
Section: Multiple Pathways For Riddingmentioning
confidence: 99%
“…This is particularly pertinent when also considering the high levels of unemployment that currently persist across Europe, the increasing costs of housing and fuel, that for many people wages have decreased in real terms, and significant welfare reform (Eurofound , Hughes , Lambie‐Mumford , Lambie‐Mumford and Dowler , Wells and Caraher ). These are just some of the conditions which have given rise to an increasing need for emergency help with food provision for many individuals and families.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, van der Horst et al's (, p.1514) study involving in‐depth interviews with food bank receivers in the Netherlands revealed that receivers often feel their experience of poverty is not taken seriously by food bank volunteers, and that ‘compulsory gratitude feels degrading, especially when the causes of the current financial situation of the household are being seen as external’. Reflecting on in‐depth qualitative research and literature analysis of the UK case, Lambie‐Mumford and Dowler (, p.1420) explain that people employ a whole range of tactics when faced with crisis, ‘including changes to shopping and eating habits, cutting back on other outgoings, and turning to family and friends for help’, and that food aid is often a last resort. There are clear implications for the ethics of consumption, whereby habits, preferences and tastes might be altered before emergency food sources are sought, with inevitable moral questions about how these decisions are made, who else in a household might be affected, and what the longer term impacts might be on everyday consumption habits such as shopping, cooking, and wasting.…”
Section: Introductionmentioning
confidence: 99%